A Survey of QoS aware and Fault Tolerant Workflow Execution in Heterogeneous Cloud Environment (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One challenging issue in recent trends of distributed environment is workflow scheduling which concentrates on satisfying different constraints of quality of service (QoS). The cloud takes application forms for workflow that contains a set of tasks which are interdependent and are used to solve enterprise and large scale scientific problems. In cloud environment, the workflow scheduling provides broad review of approaches, which are studied comprehensively. Work scheduling article gives the analysis of different workflow scheduling methods and their characteristics. Is also perform the classification based on model of execution and its objectives. Along with this, recent developments in technology like edge-cloud computing are producing new opportunities and requirements for scheduling workflow for background processing tasks like web applications, Internet of-Things (IoT), and event-driven applications in distributed environment. Workflow scheduling article also gives scheduling of workflow in cloud computing trends. At the end, it presents the future research possible direction in creating an effective utilization of resource with good performance in tolerating the faults, execution of workload in the platform of heterogeneous cloud.